Comunidade de flebotomíneos (Dipetera, Psychodidae) em área rual endêmica de leishmaniose, na região do cerrado maranhense - FREIRE, Pedro Carvalho (2016)
Original investigative work on the structure of the phlebotomine community, Diptera of the Psichodidae family. The study was carried out in a rural area of cerrado in the state of Maranhão, where leishmaniasis occurs endemic.